Bacterial immunogenic α-galactosylceramide identified in the murine large intestine: dependency on diet and inflammation - von Gerichten, Johanna; Lamprecht, Dominic; Opálka, Lukáš; Soulard, Daphnée; Marsching, Christian; Pilz, Robert; Sencio, Valentin; Herzer, Silke; Galy, Bruno; Nordström, Viola; Hopf, Carsten; Gröne, Hermann-Josef; et al. (Journal of lipid research, 2019)
The glycosphingolipid, α-galactosylceramide (αGalCer), when presented by CD1d on antigen-presenting cells, efficiently activates invariant natural killer T (iNKT) cells. Thereby, it modulates immune responses against tumors, microbial and viral infections, and autoimmune diseases. Recently, the production of αGalCer by Bacteroidetes from the human gut microbiome was elucidated. Using hydrophilic interaction chromatography coupled to MS2, we screened murine intestinal tracts to identify and quantify αGalCers, and we investigated the αGalCer response to different dietary and physiologic conditions. In both the cecum and the colon of mice, we found 1-15 pmol of αGalCer per milligram of protein; in contrast, mice lacking microbiota (germ-free mice) and fed identical diet did not harbor αGalCer. The identified αGalCer contained a β(R)-hydroxylated hexadecanoyl chain N-linked to C18-sphinganine, which differed from what has been reported with Bacteroides fragilis Unlike β-anomeric structures, but similar to αGalCers from B. fragilis, the synthetic form of the murine αGalCer induced iNKT cell activation in vitro. Last, we observed a decrease in αGalCer production in mice exposed to conditions that alter the composition of the gut microbiota, including Western type diet, colitis, and influenza A virus infection. Collectively, this study suggests that αGalCer is produced by commensals in the mouse intestine and reveals that stressful conditions causing dysbiosis alter its synthesis. The consequences of this altered production on iNKT cell-mediated local and systemic immune responses are worthy of future studies.
Keywords: Galactosylceramides; galaktosylceramidy; invariant natural killer T cells; mass spectrometry; experimental colitis; Diet; immunology; sphingolipids; tlusté střevo; influenza A virus; Inflammation; Western diet; zvířata; myši; zánět; Mice; Bacteroides fragilis; dieta; Mice, Inbred Strains; cluster of differentiation 1d; Animals; Intestine, Large; inbrední kmeny myší; bacteria; glycolipids